(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2025)
Ḥammām therapy, a traditional bathing practice with historical roots in Roman and Islamic cultures, is designed to provide both physical and therapeutic benefits through a sequence of hot, warm, and cool rooms. Fundamental to the Unani medical system, it uses a series of hot, warm, and cool exposures to enhance circulation, aid in detoxification, and treat skin and musculoskeletal disorders. The therapeutic mechanism of the Ḥammāmis based on principles of balancing bodily humors and restoring health through Tarteeb (regulating moisture) and Taskhīn (heat therapy). Although the practice offers numerous health benefits, its use requires careful consideration of individual temperaments and medical conditions. This review examines the historical evolution, architectural structure, procedural aspects, and types of Ḥammāmbaths, including their specific health benefits & modern clinical studies validating its efficacy in conditions like metabolic syndrome, cardiovascular disorders, and post-stroke rehabilitation, emphasizing its relevance in contemporary integrative medicine.